2007
DOI: 10.1002/ajmg.a.32079
|View full text |Cite
|
Sign up to set email alerts
|

A patient with the syndrome of megalencephaly, mega corpus callosum and complete lack of motor development

Abstract: The syndrome of megalencephaly, mega corpus callosum and complete lack of motor development (MCC; OMIM 603387) is an apparently rare condition since only three sporadic cases have been reported [Gohlich-Ratmann et al. (1998); Am J Med Genet 79:161-167]. We describe an additional case that was not diagnosed until age 15 months. The MRI showed generalized, severe enlargement of the corpus callosum and thickening of the cortex. The cause for the MCC syndrome is unknown and both autosomal recessive and spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Conditions associated with megalencephaly These include megalencephaly, mega corpus callosum and complete lack of motor development [33][34][35]; megalencephaly, mega corpus callosum polymicrogyria (Fig. 25) Thick corpus callosum associated with a normal head size Thick corpus callosum associated with a normal head size is reported with neurofibromatosis type I and syndrome of hypertrichosis, hyperkeratosis, abnormal corpus callosum and mental retardation; and it can be incidental, e.g., upper range of normal [38].…”
Section: Primary Conditions Associated With Thickening Of the Corpus mentioning
confidence: 99%
“…Conditions associated with megalencephaly These include megalencephaly, mega corpus callosum and complete lack of motor development [33][34][35]; megalencephaly, mega corpus callosum polymicrogyria (Fig. 25) Thick corpus callosum associated with a normal head size Thick corpus callosum associated with a normal head size is reported with neurofibromatosis type I and syndrome of hypertrichosis, hyperkeratosis, abnormal corpus callosum and mental retardation; and it can be incidental, e.g., upper range of normal [38].…”
Section: Primary Conditions Associated With Thickening Of the Corpus mentioning
confidence: 99%
“…In these reports the distribution of polymicrogyria differed between affected children. Whereas Dagli et al 2008 found generalized cortical thickening, focal thickening with incomplete opercularization was reported by Göhlich‐Ratmann et al 1998. In the patient reported by Pierson et al 2008, bilateral perisylvian polymicrogyria extending to the frontal lobes was noted whereas macrocephaly was absent (Table I).…”
Section: Discussionmentioning
confidence: 77%
“…The particular combination of megalencephaly, extensive polymicrogyria with a pachygyric appearance and mega CC, is extremely rare. Only four patients showing a similar brain morphology combined with a severely impaired motor development have been reported so far (Table I) [Göhlich‐Ratmann et al, 1998; Dagli et al, 2008]. In these reports the distribution of polymicrogyria differed between affected children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of thickened corpus callosum is not well known because it is in some cases an isolated finding [3,4]; however it is frequently associated with other brain malformations [3,[5][6][7][8][9][10]. It can be a part of syndromic conditions such as Cohen syndrome [11], Williams syndrome [12], and neurofibromatosis type 1 [13].…”
Section: Introductionmentioning
confidence: 99%